Proceedings of the 17th International Conference on World Wide Web 2008
DOI: 10.1145/1367497.1367633
|View full text |Cite
|
Sign up to set email alerts
|

Web video topic discovery and tracking via bipartite graph reinforcement model

Abstract: Automatic topic discovery and tracking on web-shared videos can greatly benefit both web service providers and end users. Most of current solutions of topic detection and tracking were done on news and cannot be directly applied on web videos, because the semantic information of web videos is much less than that of news videos. In this paper, we propose a bipartite graph model to address this issue. The bipartite graph represents the correlation between web videos and their keywords, and automatic topic discov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 18 publications
0
40
0
Order By: Relevance
“…Several efforts have focused on extracting high-quality information from social media [1,4,24,27,31]. Recent studies [21,22] showed that social media document tags are accurate content descriptors, and could be used to train a social tagging prediction system.…”
Section: Related Workmentioning
confidence: 99%
“…Several efforts have focused on extracting high-quality information from social media [1,4,24,27,31]. Recent studies [21,22] showed that social media document tags are accurate content descriptors, and could be used to train a social tagging prediction system.…”
Section: Related Workmentioning
confidence: 99%
“…Dong et al [18] proposed a method to evaluate tag relevance score by combining the probabilistic relevance score estimation and random walk-based refinement. Especially, Liu et al [9] presented a Web video topic discovery and tracking method via a bipartite graph which represents the correlation between videos and their tags. Actually, their idea is the motivation of this work.…”
Section: Related Workmentioning
confidence: 99%
“…VTR is an extension of VisualRank [6] with ideas motivated by [9]. In [9], tags and videos are also co-ranked using their correlation to refine their relevance with a specific topic.…”
Section: Proposed Approachmentioning
confidence: 99%
See 2 more Smart Citations